Intergenerational Education Mobility and the Level of Development: Evidence from Turkey - Abdurrahman Aydemir; Hakki Yazici (Institute of Labor Economics (IZA), 2017)
This paper provides two contributions to the study of intergenerational mobility. First, we render a thorough characterization of education mobility in Turkey at the national level, including a three-generation mobility analysis. We find that the education mobility is significantly lower in Turkey compared to developed economies. Second, by exploiting large regional variation in the level of economic development across Turkey, we find that intergenerational education persistence is lower for females who grow up in more developed regions. The evidence is mixed for males. Interestingly, the development level of place of residence during earlier stages of childhood has much stronger association with education mobility compared to development level of place of residence during later stages.
Keywords: J6; I2; R0; 330; intergenerational mobility; education; economic development; three generations